Significance of Medicinal Mushrooms in Integrative Oncology: A Narrative Review - Jeitler, Michael; Michalsen, Andreas; Frings, Daniela; Hübner, Marisa; Fischer, Moritz; Koppold-Liebscher, Daniela A.; Murthy, Vijay; Kessler, Christian S. (Frontiers in Pharmacology, 2020)
Medicinal mushrooms are widely used in East Asia for the treatment of various diseases, especially in complementary cancer care. While there is a growing interest in medicinal mushrooms in Western countries and an increasing number of pre-clinical studies indicate distinct anti-cancer and regenerative properties, little is known about their potential relevance for clinical practice. This review aims to provide an overview of the clinical evidence, significance and potential role of medicinal mushrooms in complementary cancer care. Scientific databases for (randomized) controlled clinical trials evaluating whole spectrum formulations of medicinal mushrooms (mushroom powder and mushroom extracts) in cancer patients during and/or after conventional oncological treatment were searched. 8 studies met our inclusion criteria (8 randomized controlled trials, 1 controlled clinical trial). The medicinal mushrooms investigated were Agaricus sylvaticus (2 trials), Agaricus blazei murill (2 trials), Antrodia cinnamomea (1 trial), Coriolus versicolor (1 trial) and Ganoderma lucidum (3 trials); all were compared to placebo and administered orally. A variety of cancer entities, outcomes and treatment durations were observed. Study results suggested beneficial effects of medicinal mushrooms, particularly quality of life and reduction of adverse effects of conventional therapies. Also, positive effects on antitumor activity and immunomodulation were reported, e.g. an increased activity of natural killer cells. In addition, results might suggest a longer survival of cancer patients receiving mushroom preparations, although in most studies this was not significant when compared to placebo. Adverse events of treatment with medicinal mushrooms were poorly reported; gastrointestinal reactions and a decrease in platelet cell count occurred in some cases. The methodological quality of most studies was generally unsatisfying and most results were insufficiently reported in several respects. Medicinal mushrooms may have a therapeutic potential for cancer patients during and after conventional oncological care with regards to quality of life, reduction of adverse effects of conventional care and possibly other surrogate parameters like immune function. There is an urgent need to investigate the safety and possible interactions of medicinal mushrooms. High-quality clinical research is warranted in order to clarify the potential of medicinal mushrooms in cancer therapy.